(untitled) (Journal of Plant Disease Sciences, 2023)
The significant millet crop grown in India is pearl millet, which has a slightly superior amino acid profile and is high in protein. Using blotter paper, four seed-borne fungus were isolated: Alternaria alternata, Curvularia penniseti, Bipolaris setariae, and Fusarium moniliforme. The fungicides and antagonists were then assessed using the poisoned food and dual culture techniques, respectively. Tebuconazole (0.1%), Copper oxychloride (0.25%) were found most effective fungicides over all other treatments for arresting the mycelial growth (100%) of all associated seed borne fungi followed by combi product Carbendazim + Mancozeb (0.25%). The most efficient fungal bioagent against seed-borne fungus among the antagonists was Trichoderma asperellum, followed by Trichoderma harzianum. In comparison to fungal antagonists, bacterial antagonists Bacillus subtilis and Pseudomonas fluorescence were shown to be less potent.